Impact of Age and Autoantibody Status on the Gene Expression of Scleroderma Fibroblasts in Response to Silica Stimulation. (September 2013) - Yang, Y.; Wei, P.; Guo, X.J.; Zhou, D.; Zhang, W.Z.; Assassi, S.; Zhou, X.D.
Environmental factors are believed to play an important role in the pathogenesis of systemic sclerosis (SSc). Silica exposure has been implicated as potentially hazardous in epidemiological studies of SSc. It can activate fibroblasts to express profibrotic genes at certain conditions. The aim of this study is to examine whether the fibroblasts of SSc patients respond to silica particles with specific gene expressions differentially from normal control fibroblasts. The fibroblasts obtained from skin biopsies of 96 SSc patients and 104 controls were examined. Silica particles were used to perturb the cultures of the fibroblasts in time-course and dose-response assays. The transcript levels of COLI A2, COL3A1, MMP1, MMP3, TIMP3 and CTGF genes of the fibroblasts were measured with quantitative RT-PCR. The results showed that the expressions of all six genes in SSc fibroblasts under silica perturbation appeared significantly different from normal control fibroblasts. In age stratified analysis, compared to control fibroblasts, SSc fibroblasts from patients at age 30–40 years and 50–60 years displayed significantly decreased expressions of MMP1 gene in all dosage assays and increased expression of COL3A1 genes started at low dosages perturbation of silica particles, respectively. In autoantibody stratified analysis, specific gene expression patterns were significantly associated with autoantibody-subgroups of fibroblasts. A common feature of SSc fibroblasts was unstable and a wide range of gene expression changes in response to silica perturbation. Our studies may suggest an altered intrinsic dynamic control in SSc fibroblasts. In addition, sensitivity and specificity of SSc fibroblasts to potentially hazardous environmental trigger is age and autoantibody-subgroup-dependent. The fibroblasts of SSc patients at age 30–60 years may be more sensitive to silica perturbation toward a profibrotic gene expression.